(3Odjd QLGd GdVHW GdLfGFj hJWHjbGJg aj GdhRGQGJ hGdgjFGJ GdMchejI aj GdeedcI GdYQHjI GdSYhOjI (B:s (3hRGQI GdOGNdjI, hRGQI GdJLGQI, hRGQI GdeGdjI, hRGQI GdSjGMI, hRGQI GdUMI, hRGQI GdehGQO GdHTQjI hGdJfejI GdGLJeGYjI, QFGSI Cef GdOhdI (B/s - (3GdeMehO, eMeO Hf YHO GdYRjRs; (3GdUeYGfj, hdjO Hf eMeOs ((3GdQjGV (B:s (3eMeO Hf YHO GdYRjR GdeMehO,s, 2020)
(3gh Odjd heQLY dcd QLd VHW LfGFj aj GdeedcI GdYQHjI GdSYhOjI hQO PcQ UaJg aj GdCfXeI GdSYhOjI, ShGA cGf aj hRGQI GdOGNdjI hbWGYGJgG GdCefjI, Ch hRGQI GdJLGQI, Ch hRGQI GdeGdjI hGdLeGQc GdSYhOjI, Ch hRGQI GdSjGMI, Ch hRGQI GdUMI hGdgjFI GdYGeI ddZPGA hGdOhGA, hcPdc aj GdMeGjI GdGLJeGYjI GdJGHYI dhRGQI GdehGQO GdHTQjI hGdJfejI GdGLJeGYjI, hCjVG aj QFGSI Cef GdOhdI, eGQS eDdag CYeGd GdVHW GdLfGFj Sfjf WhjdI ceG eGQS GdJMbjb hGdGOYGA GdYGe, h OQH GdBdGa ef QLGd GdVHW GdLfGFj aj eNJda GdJNUUGJ(B.s
(3GdUa hGdENQGL (B: (3eQcR eOGQ GdeSde(B.s
(3HHdjhLQGajI (B: (3UaMI (B374-376.s
Keywords: (3bGfhf GdELQGAGJ GdLfGFjIs -- (3GdSYhOjIs; (3GdbGfhf GdLfGFjs -- (3GdSYhOjIs; (3GdVHW GdbVGFjs -- (3GdSYhOjIs